2008
DOI: 10.1016/j.tsf.2008.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-resistant epitaxial Pb(Zr,Ti)O3 capacitors on Pt electrode with ultra-thin SrTiO3 template layers

Abstract: Lead zirconate-titanate Pb(Zr,Ti)O 3 (PZT) capacitors with Pt bottom electrodes were prepared on MgO substrates by pulsed laser deposition (PLD) technique employing SrTiO 3 (STO) template layer. Perovskite PZT thin films are prepared via stoichiometric target using the ultra-thin STO template layers while it is quite difficult 1 Present address: Kanazawa Murata Mfg., Co., Ltd., Hakusan 920-2101, Japan  Corresponding author: e-mail amorimot@ec.t.kanazawa-u.ac.jp, tel +81-76-234-4876 * Manuscript2 to obtain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The intensity of Pb 4f peaks decreased greatly with the increasing annealing temperature due to diffusion of Pb into silicon, which is consistent with what have been reported in literature. 36,37 Meanwhile, the intensity of Ti 2 p and Zr 3 d peaks did not change much with the increasing temperature. In order to study the diffusion of Pb into Si substrate, detail scans of Pb4 f, O 1 s, and Si 2 p were examined.…”
Section: Resultsmentioning
confidence: 93%
“…The intensity of Pb 4f peaks decreased greatly with the increasing annealing temperature due to diffusion of Pb into silicon, which is consistent with what have been reported in literature. 36,37 Meanwhile, the intensity of Ti 2 p and Zr 3 d peaks did not change much with the increasing temperature. In order to study the diffusion of Pb into Si substrate, detail scans of Pb4 f, O 1 s, and Si 2 p were examined.…”
Section: Resultsmentioning
confidence: 93%
“…[12][13][14]. Several researchers reported that the formation of a deleterious pyrochlore phase could be effectively suppressed by the insertion of an adequate buffer layer between platinum-coated silicon substrates and PZT, PMN-PT and PT thin films [15,16]. Since some ferroelectric thin films deposited directly on platinum coated silicon substrates often contain a considerable amount of a deleterious pyrochlore phase which is characterized by poor electrical properties; i.e., a lower dielectric constant and remnant polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Since some ferroelectric thin films deposited directly on platinum coated silicon substrates often contain a considerable amount of a deleterious pyrochlore phase which is characterized by poor electrical properties; i.e., a lower dielectric constant and remnant polarization. Takahara et al [16] reported that PZT thin films deposited directly on a platinum-coated MgO single crystal substrate by a pulsed laser deposition (PLD) technique resulted in the predominant pyrochlore phase. However, Takahara et al demonstrated that the pyrochlore phase completely disappeared when SrTiO 3 (STO) thin films acting as buffer layer were inserted into the PZT/Pt interface [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the amount of polarization charge eventually decreases below a threshold level of FeRAM device, the memory of the bit is lost. Hence, polarization loss is considered to be an important issue for the expanded FeRAM application area over wide range of temperature.As a ferroelectric material for FeRAM applications, Pb(Zr,Ti)O3 (PZT) is well known because of its high remnant polarization, low coercive field and low processing temperature [1][2][3]. However, it is known that remnant polarization in PZT film capacitors shows serious polarization loss at high temperature [4][5][6].…”
mentioning
confidence: 99%